Enterobactin Deficiency in a Coliform Mastitis Isolate Decreases Its Fitness in a Murine Model: A Preliminary Host–Pathogen Interaction Study - Vander Elst, Niels; Breyne, Koen; Steenbrugge, Jonas; Gibson, Amanda Jane; Smith, David George Emslie; Germon, Pierre; Werling, Dirk; Meyer, Evelyne (Frontiers in Veterinary Science, 2020)
Iron is an essential nutrient for bacterial growth. Therefore, bacteria have evolved chelation mechanisms to acquire iron for their survival. Enterobactin, a chelator with high affinity for the ferric ion, is secreted by Escherichia coli (E. coli) and contributes to its improved bacterial fitness. In this preliminary study, we evaluated enterobactin deficiency both in vitro and in vivo in the context of E. coli mastitis. Firstly, we showed that expression of lipocalin-2, a protein produced by the host that is able to both bind and deplete enterobactin, is increased upon E. coli infection in the cow’s mastitic mammary gland. Secondly, we demonstrated in vitro that enterobactin deficiency does not alter IL-8 expression in bovine mammary epithelial cells and its associated neutrophil recruitment. However, a significantly increased ROS production of these neutrophils was observed. Thirdly, we showed there was no significant difference in bacterial in vitro growth between the enterobactin deficient mutant and its wild type counterpart. However, when further explored in a murine model for bovine mastitis the enterobactin deficient mutant versus the wild type strain revealed a significant reduction of the bacterial load and consequently a decrease in pro-inflammatory cytokines (IL-1α, -1β, -4, -6 and -8). A reduced neutrophilic influx was also observed immunohistochemically. These findings therefore identify interference of the enterobactin iron scavenging mechanism as a potential measure to decrease the fitness of E. coli in the mastitic mammary gland.